PENGARUH JENIS PERMUKAAN TERHADAP BESARNYA LIMPASAN AIR - Cahyo Indro Saputro; Bambang Surendro; Muhammad Amin (Reviews in Civil Engineering, 2018)
The expansion of urban areas and the reduction of forest areas occur on several places in Indonesia. The Building process will effect to the land untilization. So, it needs a rule to guide the environmental balance. The purpose of the research is to find out the effect of the land surface and the slope to the flow coefficient (C).            This research was conducted using catchment area model. The measurements were done by the average of rain intensity, the soil density, volume of runoff, and the flow coefficient (C). The slope area that were used are 00, 20 and 40. The surface used soil, paving, grass, and a mixture of soil and rock with of 75%: 25% ratio.            The result showed that the slope value effected to the value of flow coefficient (C), if the slope was high then flow coefficient (C) value was high too. The result showed that the mixture of soil and rock surface had the hihghest value that is 40 slope with 0.43 coefficient value. The surface that had lowest value is grass surface on the 00 slope value with 0.11 average value of flow coefficient (C). Based on the ANOVA test results, it showed the slope surface had positive and significant effect to the flow coefficient (C) value.